Radiation‐associated sarcoma after breast cancer in a nationwide population: Increasing risk of angiosarcoma - Samuli H. Salminen; Mika M. Sampo; Tom O. Böhling; Laura Tuomikoski; Maija Tarkkanen; Carl P. Blomqvist (Cancer Medicine)
Abstract Radiation‐associated sarcoma (RAS) is a rare complication of radiation therapy (RT) to breast cancer (BC). This study explored RAS after RT to BC in a nationwide population‐based material. The Finnish Cancer Registry was queried for patients with BC treated during 1953‐2014 who were later diagnosed with a secondary sarcoma in 1953‐2014. Registry data, patient files, and sarcoma specimens were  analyzed to confirm diagnosis and location of RAS at or close to the RT target volume. A total of 132 512 patients were diagnosed with invasive BC during the study period. A subsequent sarcoma was diagnosed in 355 patients. After exclusion, 96 RAS were identified. Angiosarcoma (AS) was the most prevalent histology in 50 (52%) of 96 patients. However, the first radiation‐associated AS was diagnosed in a patient treated for BC with breast‐conserving surgery in 1984, and thereafter, the proportion of AS continuously increased. The 5‐year sarcoma‐specific survival was 75.1% for RAS treated with a curative intent. The distribution of histologic subtypes of RAS has changed during the 60 years of this registry study. The first radiation‐associated AS was diagnosed in 1989, and presently, AS is the most common histologic subtype of RAS. It is possible that changes in BC treatment strategies are influencing the characteristics of RAS.